Kedudukan Lembaga Pengawas dan Penguatan Sistem Merit Pasca Putusan MK 121/PUU-XXII/2024 - Dian Alya; Azifah Syaqila Ravadina Suhendra; Febrio Dosi Pratama; Iskandar Iskandar; Madinar Madinar (CV WAHANA PUBLIKASI, 2026)
The abolition of the State Civil Service Commission through Law No. 20 of 2023 on the State Civil Service has raised serious concerns regarding the weakening of merit system oversight and the increased risk of bureaucratic politicization. The Constitutional Court addressed this issue through Decision No. 121/PUU-XXII/2024, which declared the abolition of KASN conditionally unconstitutional and mandated the reestablishment of an independent oversight body. This study aims to analyze the urgency of establishing an independent civil service oversight body and to formulate an ideal institutional design following the Court’s ruling to ensure the continued implementation of the merit system within the government bureaucracy. The study employs a normative legal. The legal materials utilized include legislation, Constitutional Court decisions, and relevant academic literature. The findings indicate that the absence of an independent external oversight body has the potential to increase violations of civil service neutrality, the buying and selling of public office, and political interference in the appointment of public positions, particularly at the local level. This study identifies two institutional design models: the Parliamentary Oversight Satellite, which situates the oversight body within the parliamentary framework, and the Independent Administrative Commission, structured as a public legal entity with institutional autonomy, financial independence, and executive authority. In conclusion, future civil service oversight bodies must not merely function in an advisory capacity but must also possess effective enforcement authority and maintain an institutional position separate from the executive branch to ensure the realization of a professional, neutral, and integrity-driven bureaucracy.